Adherence to Adjuvant Endocrine Therapy and Associated Factors Among Patients with Breast Cancer - Tu Son, Nguyen; Thi Hong Hanh, Nguyen; Thi Thu Trang, Tran; Dinh Tien, Vu; Thi Le Hao, Hoang; Thi Lien Huong, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 1DO - 10.25073/2588-1132/vnumps.4713, 2025)
Adherence to adjuvant endocrine therapy plays an important role in the treatment of breast cancer. The study's objective was to assess the current status of adherence to adjuvant endocrine therapy in breast cancer patients and analyze some related factors. A cross-sectional study was conducted at K and Hanoi Oncology Hospital using the ARMS toolkit to assess adherence. Patient and treatment drug factors were included in regression analysis to determine the association. 863 patients agreed to participate in the study,